Verification of a new prototype design of bogie monorail frame with variation of static loading - Budi Haryanto; Makmuri Nuramin; Djoko Wahyu Karmiadji; Mustasyar Perkasa; Anwar Anwar; Budi Prasetiyo; Yudi Irawadi; Ogi Ivano; Yana Heryana; Indra Hardiman; Saeful Andhi; Wahyu Purnawirawan (Mechanical Engineering for Society and Industry, 2023)
The purpose of this study was to analyze and validate the strength of a new design monorail bogie frame. The 33 tons capacity of passenger train is supported by two bogie frames, in which each bogie frame structure should support 16.5 tons train load. A bogie frame prototype of monorail structure made of steel material JIS SS 400 was tested with 16.5 tons of static loading. Static test results showed the maximum strain value was 479 microstrain or equivalent to a stress value of 100.54 MPa. The experimental stress value was still far below the yield stress value of the material of 245 MPa. Based on the results of static testing, the design of the monorail bogie frame structure meets strength criteria and safety requirements.